ENGLISH LEARNING BASED ON MULTIPLE INTELLIGENCE IN TYPE OF LINGUISTIC INTELLIGENCE - Pradana, Agrissto Bintang Aji (DIDAKTIKA TAUHIDI: JURNAL PENDIDIKAN GURU SEKOLAH DASAR, 2018)
This study aims to describe the application of English language learning based on Multiple Intelligence Theory on the type of linguistic intelligence and student responses in following the learning of English. This research is a descriptive research, conducted in Madrasah Ibtidaiyah Muhammadiyah Special Program Kartasura. Respondents in this study were principals, English language teachers, and 34 students. Data were collected through interview (semi-structured interview), observation, and questionnaire. Data were analyzed by step (1) data reduction; (2) data display; (3) verification. The results revealed that the students as a whole showed a positive response to the learning activities. As many as 88.2% of students have motivation to participate in learning activities, 82% interested in the material, and 79% like English subjects. In conclusion that students showed high intensity of physical motion almost resembles the characteristics of students with kinesthetic and naturalistic types and apply different concepts.